2011
DOI: 10.3346/jkms.2011.26.11.1501
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Surgeon's Awareness Can Improve Osteoporosis Treatment Following Hip Fracture: A Prospective Cohort Study

Abstract: Through retrospective Jeju-cohort study at 2005, we found low rates of detection of osteoporosis (20.1%) and medication for osteoporosis (15.5%) in those who experienced hip fracture. This study was to determine the orthopedic surgeons' awareness could increase the osteoporosis treatment rate after a hip fracture and the patient barriers to osteoporosis management. We prospectively followed 208 patients older than 50 yr who were enrolled for hip fractures during 2007 in Jeju-cohort. Thirty four fractures in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…[131415] Knowledge and awareness of the health care provider could improve the level of awareness in patients with osteoporosis. [15]…”
Section: Introductionmentioning
confidence: 99%
“…[131415] Knowledge and awareness of the health care provider could improve the level of awareness in patients with osteoporosis. [15]…”
Section: Introductionmentioning
confidence: 99%
“…Hip fractures are a disabling event and an important cause of morbidity and mortality in elderly people (1-4). The majority of patients following hip fracture are treated operatively to obtain pain relief, hasten mobility, and minimize complications.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported low rates of osteoporosis treatment after hip fracture. [18,19] This result suggests that the orthopedic surgeon can perform a leading role in the prevention of further fractures. We agree that the orthopedic surgeons can serve a pivotal role in optimizing treatment, not only of the fracture, but also of the underlying disease.…”
Section: Discussionmentioning
confidence: 97%